Orfee: A bio-economic model to simulate integrated and intensive management of mixed crop-livestock farms and their greenhouse gas emissions. (October 2017) - Mosnier, Claire; Duclos, Anne; Agabriel, Jacques; Gac, Armelle
Abstract: How do we plan future sustainable livestock farming systems? Some argue that intensive, specialized systems are more efficient and emit fewer pollutants; others claim that integrated, diversified farming systems are more beneficial to both society and the environment. Bio-economic farm models can help decision-makers and researchers analyze the trade-offs among the numerous possibilities, and direct future livestock production toward greater sustainability. The Orfee model described and evaluated here was developed with this aim. It covers a broad range of beef and dairy systems and forage and crop production alternatives that may be managed with varying levels of intensity (breed, production objective, crop operations, etc.) and integration (crop rotation, organic fertilization, calving period, animal diets, etc.). Capital is also included in the optimization process, with trade-offs between production, labor, machinery and buildings. Environmental impact is assessed through potential impact on climate change. Highlights: Orfee is a bio-economic model that optimizes a function of net income under market and policy variability It simulates beef and dairy farms with a gradient of production intensification (breed, type of crops, productivity) Integration can be obtained by crop rotation, organic fertilization, calving periods and animal diets Machinery, buildings and labor are taken into account Impact on climate change is assessed